A history, evolution and application of form-based codes - Gowdy, Lauren M. (Kansas State University, 2009)
Form-based codes are gaining in popularity and provide a much needed and adequate alternative to more commonly used zoning regulations. Analysis shows the inadequacies and negative consequences that zoning regulations have created over the past 100 years of use within the United States. The focus being that traditional zoning regulations create undesired and unsustainable communities. A progression of form-based codes from their origins to the use of form-based codes today shows how they can be used to influence and shape the built environment. Further examination of the evolution of form-based codes reveals the guiding principles and elements of more modern codes. When compared to traditional zoning regulations, form-based codes can assist in designing a better quality built environment by creating more conscious, significant and sustainable places and spaces within our communities. By looking at current ways in which form-based codes are implemented we can begin to define best management practices and speculate on the future of form-based codes.
Keywords: Form-based codes; Zoning regulation alternatives; New urbanism; Urban and Regional Planning (0999)